Moisture formation in Urea Magnesium Sulphate synthesized via ball milling technique: article - Zulkefly, Nur Zhafarina; Kadri, Atikah (2019)
Higher population urge agricultural family to rise up their production in food source along with maintaining the growth of the plant as well. In order to improve nutrient in the soil so that the plant able to growth well, mechanochemical method was practiced as to synthesis of Urea Magnesium Sulphate (UMS). The UMS was synthesized based on different ratio and milling time via ball milling and the moisture content is investigated on the sample. The synthesizing is conducted based on ratio 1:1, 2:1, 1:0.7 and 1:2 of magnesium sulphate to urea with different time milling of 2, 4 and 8 minutes. The characterization of UMS is analyze by using X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) is to determine the functional group of UMS and Thermal Gravimetric Analysis (TGA) is used to identify the moisture formation in UMS. It was found that most of the sample crystallized based on XRD graph pattern. The analysis found that urea magnesium sulphate with ratio of 1:2 at 8 minutes milling time has synthesized urea magnesium sulphate. While based on the FTIR the range of IR Spectrometry adsorption between 515cm1 to 4000cm-1 and it is shown that the most of the bond is found and similar with each other in the sample. To study proximate analysis, TGA is used as to identify the moisture content which is in between 800C to 1500C. High amount of magnesium sulphate and longest milling time has the lowest amount of moisture content. As to ensure the urea magnesium sulphate is synthesized with low moisture content, the milling time should be conducted with longer period.